2013
DOI: 10.1016/j.jval.2012.10.011
|View full text |Cite
|
Sign up to set email alerts
|

An Expert on Every Street Corner? Methods for Eliciting Distributions in Geographically Dispersed Opinion Pools

Abstract: Recent publications outline developments in eliciting probabilistic opinions from clinical experts with which to inform structural assumptions and parameter estimates in health economic models. We outline approaches taken to date to elicit probabilistic distributions from experts within the health economic literature and outline the appropriate considerations and the resulting process in developing a new elicitation program with the aim of allowing low-cost elicitation of expert opinion from a heterogeneous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 8 publications
0
43
0
Order By: Relevance
“…Four of the 12 were exclusively dedicated to the description of the elicitation exercise, independent of the modelling process [12,21,26,27], and one [28] was a methodological paper which also reported an elicitation study. The rest of the studies reported the elicitation exercise with less detail, but explicitly indicated elicitation of probability distributions for a number of model parameters.…”
Section: -Summary Statisticsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four of the 12 were exclusively dedicated to the description of the elicitation exercise, independent of the modelling process [12,21,26,27], and one [28] was a methodological paper which also reported an elicitation study. The rest of the studies reported the elicitation exercise with less detail, but explicitly indicated elicitation of probability distributions for a number of model parameters.…”
Section: -Summary Statisticsmentioning
confidence: 99%
“…Two studies [12,26] report specifically selecting experts with different experiences, while in Stevenson et al [30], the experts were part of the study team. One study [28] specifically targets geographically dispersed experts, in an effort to explore the wide-spread collection of quality data. No further aspects of expert selection are reported in the studies.…”
Section: -Preparation Of the Elicitationmentioning
confidence: 99%
See 3 more Smart Citations